(untitled) (PerCursos, 2023)
When we understand that history can be written and constructed from hegemonic narratives, the need arises to think about the other voices that were possibly silenced in the writing process. The linearity and romanticism that is sometimes present in history start to be questioned, as is the case of the colonization process, which reflects in silencing and exclusions until nowaday. The “Making history” is not a neutral operation, and can segregate people or social groups, in addition to representing a form of appropriation of the other, which is named, classified and hierarchized through historical discourse. Michel de Certeau is an author who criticizes attempts to constitute the other, realized mainly by the historiographical discourse. In the same way, post-colonial thinking brings up the reflection reflection about the need for a decentered rewriting of the great imperial narratives of the past and of the deconstruction of that taken as universal, linear, different, of the reclassification of alterity. Based on this context, this essay seeks to evidence approximations of the Michel de Certeau, mainly about the work "The writing of history", with the postcolonial approach.